Matched [compact disc, unabridged] - Condie, Allyson Braithwaite (Condie, Allyson Braithwaite. Matched trilogy ;, 2010)
Cassia has always followed the autocratic Society without question. So when Xander's face is displayed on the screen at the Matching ceremony, she knows that they are the perfect mates. However, Ky Markham's face also flashed on the screen, if only briefly. Although the Society claims it was a glitch and Cassia knows she is to be with Xander, she cannot stop thinking about Ky.